2013
DOI: 10.1016/j.actaastro.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of laser ablated plumes for asteroid deflection and exploitation

Abstract: It has been theoretically demonstrated that laser ablation is effective in the potential deflection and mitigation of asteroids. However, there have been few experimental studies to support this claim. The theoretical models are currently based on assumptions regarding the laser beam diameter, the power requirement, the formation of the ejectaplume, and the potential for ejecta to contaminate and otherwise degrade any exposed surface. Recent proposals suggesting the use of a solar pumped laser, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…With reference to Figure 1, one can assume that, in general, a layer of asteroid material will undergo a transition from solid to liquid to vapour, when illuminated by the laser. This is consistent with the surface temperature registered during laboratory experiments by Gibbings et al (2013) and the triple point temperature of the materials most commonly found on S-type asteroids. In each phase, the temperature distribution and evolution will be dictated by the heat equation:…”
Section: Vaporization Of An S-type Asteroidsupporting
confidence: 77%
“…With reference to Figure 1, one can assume that, in general, a layer of asteroid material will undergo a transition from solid to liquid to vapour, when illuminated by the laser. This is consistent with the surface temperature registered during laboratory experiments by Gibbings et al (2013) and the triple point temperature of the materials most commonly found on S-type asteroids. In each phase, the temperature distribution and evolution will be dictated by the heat equation:…”
Section: Vaporization Of An S-type Asteroidsupporting
confidence: 77%
“…From experimental investigations, we found that this contamination model predicts correctly the contamination level with a sticking coefficient x s of 0.5 [10]. Over the course of the deflection action, a contamination layer will grow on the solar arrays with the degradation factor decreasing slowly from an initial value of 1.…”
Section: Contaminationmentioning
confidence: 94%
“…(37) with sample points taken in the Halton low-discrepancy sequence [17]. Figures 9,10,11,and 12 show the expectations for different The cases with defocus reduce the maximum deflection by about 3 Earth radii. We see that the fixed deflection case presents more samples with higher deflection levels.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Many significant questions such as the solar system origin can be answered by exploring the asteroids. And at the same time, the potential risk that the asteroids impact Earth can be avoided by the asteroid exploration [1].…”
Section: Introductionmentioning
confidence: 99%